Balancing Creative Freedom and Legal Boundaries: Navigating the Evolving Landscape of Entertainment Contracts - Fornia, S.I.Kom, M.I.Kom, Fornia, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2024)
This research examines the shift in the entertainment industry that challenges existing legal and contractual boundaries, with a focus on creator rights and legal protections. The dispute between Taylor Swift and Big Machine Records was the main focus, illustrating important issues related to copyright, creative control, and fair contracts in the music industry. Through this case analysis, this research highlights the importance of understanding the rights to recording masters and the strategies artists can use to regain control over their work, including re-recording their songs. The method used is a literature study, with an analysis of recording contracts, legal statements, and music industry publications. This research also examines how the media affects public perception and attitudes towards artist rights issues. The results of the study show that artists need to understand and negotiate clauses in their recording contracts, especially regarding royalty rights, contract duration, and exclusive rights, to avoid injustice. Re-recording strategies such as Taylor Swift are considered effective in regaining creative and economic control over their work. In Indonesia, the importance of education and awareness of copyright and ownership of recording masters is crucial, considering the frequent violations and injustices in recording contracts. The research offers insights into how artists in Indonesia can ensure ownership and control over their recording masters through clear agreements, contract renegotiations, and the use of re-recording rights. The legal implications and effective marketing strategies are also discussed, providing guidance for artists to strengthen their position in the music industry. As such, the study emphasizes the importance of copyright protection and fairness in recording contracts, and proposes concrete steps that artists can take to protect their creative rights and optimize the economic benefits of their work.